Mid-Term Outcome Of A Decade Of Delayed Total Cavopulmonary Connection Completion Strategy At Red Cross War Memorial Children's Hospital. - Swai, Noel (Division of General Surgery, 2024)
Background: Total cavo-pulmonary connection (TCPC) is currently the definitive palliative operation for single ventricle congenital anomalies. It is the last stage in the single ventricle pathway and can be completed following a bidirectional Glenn shunt (BGS), if a set of strict criteria are met. The TCPC is inherently an ineffective circulation, and long-term complications are inevitable. In an attempt to delay TCPC circulation-related complications, we have followed a delayed TCPC completion strategy and maintenance of forward flow at the time of bidirectional Glenn shunt circulation whenever possible. In this study, we will describe the results over the last decade. Materials and Methods. Single-centre, retrospective study from January 1, 2009, to December 31, 2018. A total of 42 patients underwent extracardiac TCPC procedures on cardiopulmonary bypass. The most common indication for TCPC was Tricuspid atresia (56%). The median age at the time of operation was 9 [Interquartile range: 7 – 11] years. The median time interval between the bidirectional Glenn shunt and TCPC procedure was 6 [IQR: 4 - 9] years. The median followup was 24 [Interquartile range: 12 – 43] months. Results: Most common postoperative morbidities were prolonged pleural effusion 22 (58%) and infection 16 (38%) which were independently risk factors for prolonged hospital or intensive care unit (ICU) stay respectively. There was no 30-day mortality, and the 1-year and 5-year survival rates were 98% and 88%, respectively. The preservation of forward flow at the time of BGS did not prolong the time interval between the two procedures. Conclusion: Delayed TCPC strategy with or without retention of forward flow at the time of bidirectional Glenn circulation has shown acceptable outcomes. In this series, we did not show any benefit in the retention of forward flow. This strategy may be ideal in a resource-limited environment. We recommend the implementation of infection and pleural drainage control management protocols to avoid prolonged ICU and hospital stays.